Effectiveness of manual therapy in improving pain and range of motion in patients with low back pain (Research, Society and Development, 2025)
Introduction: Low back pain is a prevalent and debilitating condition that affects individuals’ quality of life. Classified as either specific or non-specific, low back pain can have mechanical, inflammatory, or psychosocial origins. Manual therapy, which includes manipulation and mobilization techniques, has been studied as an effective approach for treating this condition. Objective: To analyze the effectiveness of manual therapy in the treatment of low back pain, focusing on pain relief and improvement in range of motion. Materials and Methods: A narrative literature review was conducted, with searches in electronic databases such as PubMed, BVS, SCIELO, and PEDro. Studies published in the last five years on the application of manual therapy for low back pain were included. Data analysis followed a descriptive qualitative approach, organizing the findings into thematic categories. Results: The review revealed that manual therapy, including spinal manipulation and joint mobilization techniques, is effective in reducing low back pain and improving range of motion. Techniques such as myofascial stretching were also associated with improvements in function and mobility. The integration of these techniques with interventions such as physical exercise and patient education enhances the outcomes. Final Considerations: Manual therapy emerges as an effective approach for managing low back pain, providing significant benefits in pain reduction and functional improvement. A multidisciplinary approach, incorporating psychosocial factors and integrated strategies, is essential to optimize results and promote long-term functional recovery.